Analisis Pertumbuhan Ekonomi Wilayah Kota Surakarta Tahun 2010-2013 - Widiyanti, Latif, Drs. Priyono M.Si, Dra. Retno Woro Kaeksi (2015)
Surakarta city lies between the strategic lines that connect the transportation of Central Java, Yogyakarta and East Java. The transport links are very beneficial for the economy of Surakarta. The existence of the centers of community activity such as terminals, markets, stations, airports and tourist attractions history is unbelievably encouraging the development of sectors of trade and services. Surakarta economic growth or development of the past twelve years tends to increase except in 2008 and 2013. The decline service sector, resulting in a decrease in economic growth in 2013. In this study, the selection of Surakarta as an area of research because it is an administrative region Surakarta narrow and limited natural resources, it is proved by the population working in agriculture is very little compared with other sectors. Their center of activities that encourage trade and tourism activity raises a question of how its role in the economy and the spread in Surakarta. The aim of this study is to examine the pattern of economic growth sub-districts in the city of Surakarta in 2010-2013 and examines the role of the leading sectors of Surakarta, Central Java on the Economy 2010-2013. The method used in this research is qualitative methods of analysis using a combination of qualitative and quantitative approaches, with a greater proportion of quantitative methods whereas qualitative methods are quantitative verification of the results. The data used is secondary data taken from previous research or related government agencies. Data available to analized to determine economic growth, LQ (Location Quotient), and the spread of economic growth in Surakarta. The pattern of economic growth sub-districts in Surakarta years 2010-2013 are affected by trade, hotels and restaurants sector, manufacturing, construction, and service sectors. this happens in four sub-districts Serengan, District POND Market, District Banjarsari, and District Laweyan, while the District Jebres growth patterns influenced by the manufacturing sector. The role of the sector in economic growth caused by the economic centers that exist. Surakarta leading sectors namely trade, hotels and restaurants sector, the services sector and the construction sector into a sector basis to the economy of Central Java. The manufacturing sector is the dominant sector Surakarta which does not include the contribution base below the sector average on the economy of Central Java.